Working women stories of strife, struggle and survival - Naidoo, K. (Kogilam), 1956-; Patel, Fay.; Sage eBooks (New Delhi ; London : SAGE, 2009)
This book contains narratives pertaining to the challenges, struggles and success stories of women in the workplace who come from diverse cultures and social backgrounds. The essays discuss the struggles of women who were marginalised but who fought for recognition, dignity, and respect in their workplaces and personal lives.
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: Women -- Employment; Women -- Psychology; Women -- History; Electronic books